2015
DOI: 10.1002/etc.3050
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and gastrointestinal in vivo biotransformation rates of hydrophobic chemicals in fish

Abstract: To improve current bioaccumulation assessment methods, a methodology is developed, applied, and investigated for measuring in vivo biotransformation rates of hydrophobic organic substances in the body (soma) and gastrointestinal tract of the fish. The method resembles the Organisation for Economic Co-operation and Development (OECD) 305 dietary bioaccumulation test but includes reference chemicals to determine both somatic and gastrointestinal biotransformation rates of test chemicals. Somatic biotransformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(115 citation statements)
references
References 37 publications
8
107
0
Order By: Relevance
“…Previous work by Gobas et al reviewed empirical measurements of assimilation efficiency in the literature and concluded that dietary assimilation efficiency is initially independent of log K OW and starts decreasing at log K OW of 6 for a range of hydrophobic organic chemicals because of reduced bioavailability and steric hindrance in crossing biological membranes. The values predicted by the Gobas et al and Lo et al models are plotted in Figure B. In these nonlinear models, assimilation efficiency (α) is presented as α = (2 + 3 × 10 −7 × K OW ) −1 and α = (1.9 + 5.6 × 10 −9 x K OW ) −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work by Gobas et al reviewed empirical measurements of assimilation efficiency in the literature and concluded that dietary assimilation efficiency is initially independent of log K OW and starts decreasing at log K OW of 6 for a range of hydrophobic organic chemicals because of reduced bioavailability and steric hindrance in crossing biological membranes. The values predicted by the Gobas et al and Lo et al models are plotted in Figure B. In these nonlinear models, assimilation efficiency (α) is presented as α = (2 + 3 × 10 −7 × K OW ) −1 and α = (1.9 + 5.6 × 10 −9 x K OW ) −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The values predicted by the Gobas et al model were derived by fitting a nonlinear correlation to empirical data from various fish species that may not have the cap ability to predict variations in fish species, feeding rate, and diet type and quality, as well as food concentration. Using the relationship derived from one species and size (rainbow trout) by Lo et al led to improved predictions (1– R 2 = 0.51) compared with the relationship derived for multiple species and sizes by Gobas et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average feeding rate was 0.012 ± 0.002 g dry food/g wet fish/d, and the growth dilution rate constant for the test fish was 0.0066 ± 0.0012 d −1 and 0.0066 ± 0.0015 d −1 for the control fish. That study involved simultaneous dietary exposure to 7 reference chemicals (i.e., 1,2,4,5‐tetrachlorobenzene; pentachlorobenzene [PCBz]; hexachlorobenzene [HCBz]: 2,2′,5,5′‐PCB [PCB 52]; 2,2′,4,4′,6,6′‐PCB [PCB 155]; 2,2′,4,4′,5,5′‐PCB [PCB 153]; and 2,2′,3,3′,4,4′,5′,5′,6,6′‐PCB [PCB 209]), which were assumed not to be biotransformed significantly, and 8 test chemicals (i.e., 1,2,3,4‐tetramethyl benzene; β‐hexachlorocyclohexane [β‐HCH]; trans‐decalin; 9‐methylanthracene; chrysene; hexylcyclohexane; 2,6‐dimethyldecane; and benzo[ a ]pyrene), which were expected to be biotransformed. The authors measured depuration rate constants over a period of 114 d and used linear regression of the natural logarithm of the concentrations of the test and reference chemicals versus time to determine the depuration rate constant for the reference and test chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…The endpoint in this new test is the biomagnification factor (BMF), which is considered to be a meaningful measure of the potential for a chemical to undergo dietary biomagnification in the environment [5,6]. However, there are as yet limited experimental BMF data, and many researchers and regulators are still trying to identify appropriate strategies for assessing the bioaccumulation potential of chemicals using dietary exposure tests [10][11][12][13][14]. However, there are as yet limited experimental BMF data, and many researchers and regulators are still trying to identify appropriate strategies for assessing the bioaccumulation potential of chemicals using dietary exposure tests [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%